Perancangan Penempatan Access Point untuk Jaringan Wifi Pada Kereta Api Penumpang - Prastise Titahningsih; Rakhmadhany Primananda; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The application of Wi-Fi networks is getting easier, even now it can be found on some public transport. So it is not impossible if applied to passenger trains. However, the implementation of passenger trains may be confronted by several issues such as coverage area (railway) which is made of iron and steel. As in previous research, observing railway propagation losses is important because it affects signal strength (We, Ito, Yokoyama, Tseng, Sagawa, Ogasawara) and based on research on wifi network optimization in the recovery room there are several aspects that need Be considered as aspect of propagation, and coverage area aspect. (Widyaningsih, 2013) Therefore it is necessary to observe and calculate the appropriate, so as to produce an effective design. Up to the furthest distance of 21 meters the Link Budget calculator the RSL value is -43 dBm and SOM is 51 dB, with the value known that the radiated signal can spread well. And for the calculation of the number of Access Point based on the reach of the Access Point and the capacity of the client obtained at least 3 Access Point that can meet the needs in passenger trains. And from the application of the simulation with the placement of 3 Access Point, with a maximum transmit power of 18 dBm and also the application of different channels, has resulted in an average value of RSSI -35 dBm to -55 dBm, which with the value of signal characteristics interpreted in very good (Excellent).